A Bond Between Man and Woman Religiosity, Moral Foundations, and Same-Sex Marriage Attitudes in the Philippines. - Ochoa, D. P.
Same-sex marriage in the Philippines remains a highly contentious issue due to the infuence of religion in this predominantly Catholic country, where it is often framed as an issue of morality. However, the psychological underpinnings of this religious infuence still merits further exploration. Thus, we examined the role of religious behaviors and moral foundations in predicting attitudes toward same-sex marriage among Filipinos. Data from 385 participants revealed that the particular behavior of reading the main sacred text of one?s religion, rather than the often-used predictor of religious attendance predicts negative attitudes. Beyond these religious variables, the moral foundation of Purity/sanctity also predicts negative attitudes. Recommendations for further research and possible implications on attitude change are discussed in light of these findings.